Sunscreen cosmetic composition and preparation method thereof

By preparing the DBR total reflective structure and nanosilver lattice mismatch mechanism on the polyhedral structure of nano zinc oxide microspheres, the aesthetic problem of inorganic sunscreen when used on the skin is solved, and the reflection and absorption capacity of ultraviolet rays is improved, reducing the probability of biotoxic damage.

CN119523824AActive Publication Date: 2025-02-28GUANGZHOU WEIHONGQI BIOTECHNOLOGY CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411519925.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-28
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

Existing inorganic sunscreens can easily lead to a chalky appearance when used on the skin, especially in dark skin individuals, which are not beautiful. At the same time, organic sunscreens are harmful to the environment and skin-sensitive people.

Method used

Nanozinc oxide microspheres are used as cores to form a polyhedral structure through annealing treatment, and a DBR total reflective structure is prepared on its surface. Combined with the nano-silver lattice mismatch mechanism, the reflection ability of UVA and UVB ultraviolet rays is enhanced.

Benefits of technology

It improves the reflection and absorption capacity of ultraviolet rays, reduces the penetration rate and the probability of biotoxic damage, and reduces the use of physical sunscreens, improving the aesthetics of cosmetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119523824A_ABST
    Figure CN119523824A_ABST
Patent Text Reader

Abstract

The invention discloses a sunscreen cosmetic composition and a preparation method thereof, and the sunscreen cosmetic composition comprises the following components: 20-60 parts of a physical sunscreen agent, 0-30 parts of a chemical sunscreen agent, 0.01-1 part of an antioxidant, 5-20 parts of grease, 5-15 parts of a humectant, 1-5 parts of an emulsifier, 10-30 parts of absolute ethyl alcohol and 0.1-3 parts of other additives. According to the physical sun-screening agent, polyhedral nano-zinc oxide serves as a core, angular nano-zinc oxide can extend on the surface, and the polyhedral nano-zinc oxide and the angular nano-zinc oxide are coated with a multilayer SiO2 / TiO2 periodic structure to form a shell-core structure with the zinc oxide core coated with a total reflection film. The core-shell structure realizes weakening of ultraviolet rays through multiple functions of reflection, absorption and scattering, the angular nano-zinc oxide structure can improve an emergent angle to facilitate reflection of light rays, the apparent diameter of the nanospheres is increased, the probability that the nano-powder permeates into the skin is reduced, and the biotoxicity of the sunscreen product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of isolation preparations, and in particular relates to a sunscreen cosmetic composition and a preparation method thereof. Background Art

[0002] Ultraviolet (UV) radiation is the main cause of skin cancer and can also cause erythema and photoaging. Photoprotection is used to protect the skin from the negative effects of these UV radiations, and sunscreen is an important part of the photoprotection strategy.

[0003] Existing sunscreen methods are divided into two types: physical sunscreen (inorganic sunscreen) and chemical sunscreen (organic sunscreen). Organic sunscreens are harmful to the environment due to their energy-absorbing chemical substances, especially to coral reefs, and will also remain in the water supply system and aquatic animals. For people with sensitive skin, this chemical substance is also prone to cause epidermal allergic reactions. Therefore, inorganic sunscreens have become the mainstream research direction.

[0004] Currently, there are two types of inorganic sunscreens that are recognized and approved: titanium dioxide and zinc oxide. They absorb, reflect and refract ultraviolet photons, but mainly absorb ultraviolet radiation to exert their light protection effect, and the sun protection effect can reach SPF50. However, too thick a coating will leave a white chalky appearance on the skin, which is particularly obvious in individuals with dark skin and is not conducive to aesthetics. Therefore, how to balance the sun protection ability and aesthetic ability is an important research direction in the industry. In order to achieve this effect, the existing technology mostly uses a shell-core structure sunscreen, in which the shell is an organic material, which wraps the inorganic nanocore, and multiple combinations exert the ultraviolet absorption function, thereby reducing the use of inorganic sunscreens or improving the shortcomings of using a single inorganic core material. There is also a design in which the outer shell is inorganic and the inner shell is organic. A brief description of the existing technology in the corresponding field is as follows: CN201310046158.8 modifies the surface of titanium dioxide core with hyaluronic acid gel to increase the moisture retention and affinity of the skin.

[0005] CN202011445169.X uses titanium dioxide as the outer shell, and a chitosan three-dimensional network polymer chain grafted with 2-hydroxybenzophenone with ultraviolet absorption ability is placed in the inner cavity to achieve the effects of increasing the ultraviolet path in the inner cavity and dual absorption of organic sunscreens.

[0006] CN202210020016.3 adopts the structure of nano ZnO@zinc borate@guar gum composite gel to achieve multiple sun protection functions, and the preparation of zinc borate meets the requirements of high sun protection level.

[0007] CN202110362354.0 uses commercial physical sunscreen zinc oxide and titanium dioxide nanoparticles as the core and natural polyphenol resveratrol functionalized polyphosphazene as the coating layer to form a core-shell structure, which avoids direct contact between the inorganic core with active groups and the skin, while providing the sunscreen effect of a natural sunscreen.

[0008] CN201110226078.1 adopts a composite material structure consisting of titanium dioxide and zinc oxide, with zinc oxide as the core and titanium dioxide as the shell, which enhances the dispersion ability of nano zinc oxide.

[0009] CN201710472702.3 uses a large number of nano-scale sunscreen particles as the outer layer to wrap a micron-scale carrier microsphere. This structure gives the hybrid microsphere a concave-convex surface for light reflection and scattering, increases the surface area of ​​the microsphere, and can also utilize the sunscreen particles in the outer layer to absorb ultraviolet rays. It is a hybrid microsphere with both physical and chemical sunscreen effects.

[0010] There are also inorganic-inorganic shell-core structures, organic-organic shell-core structures, etc., in order to achieve multiple sun protection functions.

[0011] The design of sunscreens with different functions on the market shows the huge potential of the core-shell structure. Therefore, on this basis, the present invention further improves the use effect in related fields to meet various use requirements. Summary of the invention

[0012] In view of the problems in the related art, the present invention proposes a lightweight insulating column and a preparation method thereof to overcome the above-mentioned technical problems existing in the existing related art.

[0013] The technical solution of the present invention is achieved by using nano zinc oxide microspheres as cores, improving the surface crystal plane preferential orientation by annealing the microspheres to form a polyhedron, and preparing a DBR total reflection structure on the polyhedron, thereby enhancing the total reflection ability of UVA and UVB ultraviolet rays. A further solution is based on the polyhedron with preferential crystal plane orientation, by introducing the nano silver lattice mismatch mechanism, further epitaxial angular nano zinc oxide, covering it with a DBR total reflection structure, and preparing an optical structure with incident angle constraint, which is used to reduce the penetration rate of axial incident light and enhance the emission rate of reflected light, thereby reducing the amount of skin damage caused by ultraviolet rays. The specific content of the invention is as follows: A sunscreen cosmetic composition comprises the following components: 20-60 parts of physical sunscreen, 0-30 parts of chemical sunscreen, 0.01-1 parts of antioxidant, 5-20 parts of oil, 5-15 parts of moisturizer, 1-5 parts of emulsifier, 10-30 parts of anhydrous ethanol and 0.1-3 parts of other additives.

[0014] Preferably, the physical sunscreen agent is composed of polyhedral nano zinc oxide microspheres as cores, and the polyhedral nano zinc oxide microspheres are coated with a multilayer SiO2@TiO2 periodic structure to form a core-shell structure in which a total reflection film coats the zinc oxide core.

[0015] More preferably, the thickness of the SiO2 single layer is 20-40 nm, the thickness of the TiO2 single layer is 10-30 nm, and the particle size of the polyhedral nano zinc oxide microspheres is 50-70 nm.

[0016] More preferably, the optical refractive index of the SiO2 is less than 1.55, forming a light-scarce medium with a periodic structure.

[0017] More preferably, the optical refractive index of the TiO2 is greater than or equal to 2.50, forming an optically dense medium with a periodic structure.

[0018] More preferably, the optical refractive index of the zinc oxide is 1.9 to 2.1, forming an ultraviolet absorbing core.

[0019] Preferably, a nanosilver quantum dot defect layer is prepared on the surface of the polyhedral nano zinc oxide microspheres, angular nano zinc oxide is epitaxially grown on the defect layer, and then a multilayer SiO2 / TiO2 periodic structure is coated.

[0020] Preferably, the chemical sunscreen is one or more of a UVA sunscreen and a UVB sunscreen.

[0021] More preferably, the UVA sunscreen is composed of one or more of bis-ethylhexyloxyphenol methoxyphenyl triazine, butyl methoxydibenzoylmethane, diethylaminohydroxybenzoyl hexyl benzoate, and butyl methoxybenzophenone, and the UVB sunscreen is composed of one or more of phenylbenzimidazole sulfonic acid, ethylhexyl salicylate, octyl salicylate, ethylhexyl methoxycinnamate, octyl dimethyl para-aminobenzoate, homosalate, polysiloxane, and octyl triazone.

[0022] Preferably, the antioxidant is one or more of propylparaben, methylparaben, phenoxyethanol, benzyl alcohol, bis(hydroxymethyl)imidazolidinyl urea, and iodopropynyl butylcarbamate.

[0023] Preferably, the oil is composed of one or more of dicaprylyl carbonate, dipropylene glycol dibenzoate, caprylyl polymethicone, cyclopentasiloxane, and tridecyl stearate.

[0024] Preferably, the moisturizing agent is composed of one or more of glycerin, propylene glycol, butylene glycol, betaine, panthenol, and sodium hyaluronate.

[0025] Preferably, the emulsifier is one or more of glyceryl stearate, polyglyceryl-3 diisostearate, cetearyl glucoside, and sorbitan olivate.

[0026] Preferably, the other additives are one or more of a soothing agent, an anti-allergic agent, a complexing agent, a cross-linking agent, and a fragrance.

[0027] More preferably, the optical refractive index of the chemical sunscreen, antioxidant, oil, moisturizer, emulsifier and other additives is less than 1.55.

[0028] More preferably, the refractive index of the outermost shell layer in step S4 is greater than the refractive index of other components of the cosmetic composition.

[0029] More preferably, the final shell material in step S4 is TiO2.

[0030] This scheme also discloses a method for preparing a sunscreen cosmetic composition, comprising the following steps: S1: Synthesize nano zinc oxide microspheres by hydrothermal method, and form polyhedral nano zinc oxide microspheres by high temperature annealing in inert gas; S2: hydrothermal coating of SiO2 to form ZnO@SiO2 composite nanoparticles; S3: hydrothermal coating of TiO2 to form ZnO@SiO2@TiO2 composite nanoparticles; S4: Repeat steps S2 and S3 to form ZnO@DBR composite nanoparticles with a SiO2 / TiO2 composite layer having a stacking period greater than 2; S5: 20-60 parts of ZnO@DBR composite nanoparticles as physical sunscreen are mixed with 0-30 parts of chemical sunscreen, 0.01-1 parts of antioxidant, 5-20 parts of oil, 5-15 parts of moisturizer, 1-5 parts of emulsifier, 10-30 parts of anhydrous ethanol and 0.1-3 parts of other additives to prepare a sunscreen cosmetic composition.

[0031] Preferably, the zinc source used in step S1 is one or more of zinc nitrate, zinc acetate and zinc chloride.

[0032] More preferably, the molar concentration ratio of the ingredients used in the hydrothermal method is zinc nitrate hexahydrate: triethanolamine = 2:1, and deionized water is used as the solvent.

[0033] More preferably, the hydrothermal reaction temperature of the nano zinc oxide microspheres is 150-180° C., and the reaction time is 2-4 hours.

[0034] More preferably, the nano zinc oxide microspheres are annealed and calcined at 400-600° C. for 2-3 hours in an inert atmosphere to prepare polyhedral nano zinc oxide microspheres.

[0035] More preferably, the inert atmosphere is N2.

[0036] Preferably, the silicon source used in step S2 is one or more of tetraethyl orthosilicate, rice husk ash, and water glass.

[0037] More preferably, the silicon source is tetraethyl orthosilicate.

[0038] More preferably, the molar concentration ratio of the ingredients used in the hydrothermal method is polyhedral nano zinc oxide microspheres: tetraethyl orthosilicate: concentrated ammonia water = 40-60: 1-3: 4-8, and isopropanol is used as the solvent.

[0039] More preferably, KH550 silane coupling agent is used to disperse the polyhedral nano zinc oxide microspheres in the hydrothermal synthesis process.

[0040] More preferably, the hydrothermal reaction process temperature is 120-140° C., and the reaction time is 1-2 h.

[0041] More preferably, a water bath at 40-50° C. is used to homogenize the solutions during the hydrothermal synthesis process.

[0042] Preferably, the titanium source used in step S3 is one or more of tetrabutyl titanate, titanium tetrachloride, and titanium sulfate.

[0043] More preferably, the titanium source is tetrabutyl titanate.

[0044] More preferably, the hydrothermal reaction adopts a molar concentration ratio of ZnO@SiO2 composite nanoparticles: tetrabutyl titanate: diethanolamine = 40-60: 3-6: 1-2, and anhydrous ethanol is used as the solvent.

[0045] More preferably, the hydrothermal method uses anhydrous ethanol as the solution, and the homogenizing stirring time is 60 to 90 minutes.

[0046] More preferably, the hydrothermal reaction process temperature is 180-200° C. and the reaction time is 2-4 hours.

[0047] Preferably, the step S4 repeats the steps S2 and S3 to form a SiO2 / TiO2 total reflection shell layer with a superposition period greater than 2.

[0048] More preferably, the period is 2 to 4 groups, and the total thickness does not exceed 400 nm.

[0049] Preferably, between the step S1 and the step S2, the following steps are also included: S1-1: Preparation of silver nanoparticles by hydrothermal method on the surface of polyhedral nano-zinc oxide microspheres to prepare lattice-mismatched growth surfaces; S1-2: hydrothermally epitaxially grow angular nano-zinc oxide columns on the growth surface.

[0050] Preferably, in step S1-1, the nanosilver quantum dots are prepared by hydrothermal synthesis, using silver nitrate as the silver source.

[0051] More preferably, the hydrothermal reaction adopts a molar concentration ratio of polyhedral nano zinc oxide microspheres: silver nitrate: hexadecyltrimethylammonium bromide: PVP=40-60:0.4-1:3-6:10:15, and ethylene glycol is used as the solvent.

[0052] More preferably, the dripping rate of the ethylene glycol solution of PVP is 0.3-0.5 ml / min.

[0053] More preferably, the hydrothermal reaction process temperature is 150-170° C., and the reaction time is 60-90 min.

[0054] More preferably, the nano silver quantum dots are attached to the surface of the polyhedral nano zinc oxide microspheres in a discrete manner.

[0055] Preferably, the zinc source used in step S1-2 is one or more of zinc nitrate, zinc acetate and zinc chloride.

[0056] More preferably, the molar concentration ratio of ingredients used in the hydrothermal method is quantum dot composite nanoparticles: zinc nitrate hexahydrate: hexamethylenetetramine: ethylenediamine = 10-15: 5-7: 7-9: 10-15, and deionized water is used as the solvent.

[0057] More preferably, the hydrothermal reaction temperature of the nano zinc oxide microspheres is 90-110° C., and the reaction time is 2-3 hours.

[0058] More preferably, the ingredients are homogenized in a solvent by ultrasonic vibration.

[0059] More preferably, the angular nano zinc oxide column crystal growth orientation is (0001) plane.

[0060] Beneficial effects of the present invention: Compared with the prior art, the present invention forms a polyhedron by preferentially processing the crystal orientation of nano zinc oxide microspheres, and prepares a DBR total reflection structure based on the plane characteristics of the polyhedron, thereby enhancing the reflection ability of UVA and UVB ultraviolet rays, and part of the transmitted light is bound in the zinc oxide microsphere core by the DBR total reflection structure, and the absorption capacity of the nano zinc oxide microspheres is used to further complete the processing of ultraviolet rays.

[0061] Furthermore, the present invention improves the emission angle of ultraviolet rays, increases the emission rate, and reduces the penetration rate by introducing an angular nano zinc oxide structure.

[0062] Furthermore, the angular nano zinc oxide structure introduced in the present invention increases the particle size of the nano microspheres and reduces the probability of biological toxicity damage caused by penetrating the skin.

[0063] Ultimately, on the basis of improving the ability to reflect, absorb and scatter ultraviolet rays, the use of physical sunscreens can be reduced and the white spot effect of cosmetics can be weakened. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0065] Figure 1 This is a SEM image of the nano zinc oxide microspheres prepared in Example 1 of the present invention before calcination.

[0066] Figure 2 This is a SEM image of the nano zinc oxide microspheres prepared in Example 1 of the present invention after calcination.

[0067] Figure 3 This is a theoretical schematic diagram of the structure of nano zinc oxide microspheres prepared in Example 1 of the present invention.

[0068] Figure 4 This is the SEM image of the composite nanoparticles prepared in Example 2 of the present invention.

[0069] Figure 5 This is a theoretical schematic diagram of the structure of nano zinc oxide microspheres prepared in Example 2 of the present invention.

[0070] Figure 6 Ultraviolet reflection spectra of the ZnO@DBR composite nanoparticles and the spherical ZnO@DBR composite nanoparticles prepared in Example 1 of the present invention.

[0071] Among them, 1 is a polyhedral nano zinc oxide microsphere, 2 is the first SiO2 shell layer, 3 is the second TiO2 shell layer, 4 is the Nth SiO2 shell layer, 5 is the Nth TiO2 shell layer, 6 is a mixed layer of other cosmetic components, 7 is a nano silver quantum dot defect layer, and 8 is an angular nano zinc oxide column. DETAILED DESCRIPTION

[0072] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0073] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0074] Embodiment 1, the preparation of sunscreen cosmetic composition comprises the following steps: S1: Preparation of polyhedral nano zinc oxide microspheres. Prepare a 0.2 mol / L zinc nitrate hexahydrate solution by stirring and completely dissolving it in deionized water, then slowly drip 0.15 mol / L triethanolamine while stirring to obtain a precursor solution A, transfer the precursor solution A into a high-pressure reactor, react at 160°C for 3 hours, cool naturally to room temperature, filter the precipitate, wash and dry it, and then anneal it at 450°C in a resistance furnace for 2 hours to prepare polyhedral nano zinc oxide microspheres with a particle size of 50 to 60 nm; S2: Preparation of SiO2-coated polyhedral nano zinc oxide microspheres. Add 0.3 mol / L polyhedral nano zinc oxide microspheres and 0.03 mol / L silane coupling agent KH550 to 0.6 mol / L isopropanol, place it in a 40°C water bath, stir and mix evenly, add 10 mol / L deionized water, 0.03 mol / L concentrated ammonia water, and 0.01 mol / L tetraethyl orthosilicate in sequence, stir evenly at 40°C to obtain precursor solution B, transfer precursor solution B to a high-pressure reactor, react at 120°C for 1h, cool naturally to room temperature, filter the precipitate, wash and dry, and obtain ZnO@SiO2 composite nanoparticles with an average shell thickness of 35nm; S3: Preparation of TiO2-coated ZnO@SiO2 composite nanoparticles. 0.01mol / L diethanolamine, 0.2mol / L ZnO@SiO2 composite nanoparticles, and 0.0153mol / L tetrabutyl titanate were added to 0.5mol / L anhydrous ethanol, stirred to dissolve the tetrabutyl titanate, and then stirred for 60min to obtain a precursor solution C, which was transferred to a high-pressure reactor and reacted at 180°C for 4h. The solution was naturally cooled to room temperature, and the precipitate was filtered, washed, and dried to obtain ZnO@SiO2@TiO2 composite nanoparticles with an average shell thickness of 25nm. S4: Taking the SiO2@TiO2 shell layer formed by a single S2 and S3 as one group, repeating the S2 and S3 steps to form three groups of SiO2 / TiO2 composite layers, the outermost shell layer is a TiO2 layer, forming ZnO@DBR composite nanoparticles with a total shell thickness of 120nm, and the particle size of the ZnO@DBR composite nanoparticles is 230nm~250nm; S5: First, 3 parts of glyceryl stearate, 10 parts of glycerol, and 20 parts of anhydrous ethanol were mixed by mechanical stirring, and then 15 parts of dicaprylyl carbonate, 8 parts of bis-ethylhexyloxyphenol methoxyphenyl triazine, and 8 parts of ethylhexyl methoxycinnamate were added. Finally, 40 parts of ZnO@DBR composite nanoparticles and 0.5 parts of aloe vera soothing agent were added, and the inorganic nanoparticles were homogenized using a planetary vacuum mixer.

[0075] The filling degree in the autoclave used for the preparation in this embodiment is 60%, the prepared ZnO is wurtzite type, with a refractive index of 1.9-2.0 and a particle size of 50-60nm, the prepared SiO2 is α-quartz, with a refractive index of 1.54-1.55, a thickness of 30-40nm, and an average of 35nm, the prepared TiO2 layer is anatase type, with a refractive index of 2.45-2.55, a thickness of 20-30nm, and an average of 25nm, and the refractive index of the aloe vera soothing agent used is less than 1.5.

[0076] Figure 1 This is the SEM image of the microspheres before annealing. Figure 2 The SEM image of the microsphere after annealing. Annealing causes the regrowth of crystals, thereby weakening the macroscopic defects on the surface of the microsphere caused by lattice mismatch and dislocation.

[0077] Figure 3 The schematic diagram of the structure theory of this embodiment. Finally, 1 is a polyhedral nano zinc oxide microsphere, 2 is the first layer of SiO2 shell, 3 is the second layer of TiO2 shell, 4 is the third layer of SiO2 shell, 5 is the third layer of TiO2 shell, and 6 is a mixed layer of other cosmetic components. The equivalent DBR structure of the ultraviolet light path is a 4-fold structure, part of which is reflected by the DBR structure and part enters the ZnO core and is absorbed. This structure filters ultraviolet light of 310-400nm (see Figure 6 polyhedral lines).

[0078] Embodiment 2, the preparation of sunscreen cosmetic composition comprises the following steps: S1: Preparation of polyhedral nano zinc oxide microspheres. Prepare a 0.4 mol / L zinc nitrate hexahydrate solution by stirring and completely dissolving it in deionized water, then slowly drip 0.2 mol / L triethanolamine while stirring to obtain a precursor solution A, transfer the precursor solution A into a high-pressure reactor, react at 180°C for 4 hours, cool naturally to room temperature, filter the precipitate, wash and dry it, and then calcine it in a resistance furnace at 500°C for 2.5 hours to prepare polyhedral nano zinc oxide microspheres with a particle size of 60-70 nm; S1-1: Preparation of nanosilver quantum dots on the surface of polyhedral nano zinc oxide microspheres. Prepare ethylene glycol solution D containing 0.3 mol / L polyhedral nano zinc oxide microspheres, 0.005 mol / L silver nitrate, and 0.03 mol / L hexadecyltrimethylammonium bromide, and drip 0.05 mol / L PVP ethylene glycol solution E into solution D at a rate of 0.3 ml / min. After the dripping is completed, the solution turns dark brown to obtain a precursor solution F. Place the precursor solution F in an autoclave at 160°C for 70 minutes, filter, wash, and dry to prepare a polyhedral nano zinc oxide microsphere attached with nanosilver quantum dots, which is defined as quantum dot composite nanoparticles; S1-2: Preparation of angular nano zinc oxide columns. A deionized water solution containing 0.075 mol / L quantum dot composite nanoparticles, 0.035 mol / L zinc nitrate and 0.045 mol / L hexamethylenetetramine was prepared under ultrasonic vibration conditions, stirred for 30 min, and then a deionized water solution of 0.05 / L ethylenediamine was slowly dropped to form a precursor solution G, which was placed in a high-pressure reactor, reacted in a water bath at 100°C for 2 h, filtered, washed and dried to form angular nano zinc oxide microspheres.

[0079] S2: SiO2 coated angular nano zinc oxide microspheres. Add 0.2 mol / L angular nano zinc oxide microspheres and 0.03 mol / L silane coupling agent KH550 to 0.8 mol / L isopropanol, place it in a 50°C water bath, stir and mix evenly, add 14 mol / L deionized water, 0.04 mol / L concentrated ammonia water, and 0.015 mol / L tetraethyl orthosilicate in sequence, stir evenly at 40°C to obtain precursor solution B, transfer precursor solution B to a high-pressure reactor, react at 140°C for 2h, cool naturally to room temperature, filter the precipitate, wash and dry, and obtain ZnO@SiO2 composite nanoparticles with a coating shell thickness of 20 to 40nm; S3: ZnO@SiO2 composite nanoparticles prepared by coating S2 with TiO2. 0.01mol / L diethanolamine, 0.3mol / L ZnO@SiO2 composite nanoparticles, and 0.02mol / L tetrabutyl titanate were added to 0.5mol / L anhydrous ethanol, stirred to dissolve the tetrabutyl titanate, and then stirred for 90min to obtain a precursor solution C, which was transferred to a high-pressure reactor and reacted at 190°C for 3h. The solution was naturally cooled to room temperature, and the precipitate was filtered, washed, and dried to obtain ZnO@SiO2@TiO2 composite nanoparticles with a coating shell thickness of 10 to 30nm. S4: Taking the SiO2@TiO2 shell layer formed by single S2 and S3 as one group, repeating S2 and S3 steps to form two groups of SiO2 / TiO2 composite layers, the outermost shell layer is a TiO2 layer, forming spherical ZnO@DBR composite nanoparticles with a total shell thickness of 120nm, and the particle size of the spherical ZnO@DBR composite nanoparticles is 300nm~350nm; S5: First, 5 parts of sorbitan olivate, 10 parts of sodium hyaluronate, and 30 parts of anhydrous ethanol were mechanically stirred and mixed, and then 15 parts of octyl polymethylsiloxane, 5 parts of butyl methoxybenzophenone, and 5 parts of octyl salicylate were added. Finally, 30 parts of ZnO@DBR composite nanoparticles, 1 part of aloe vera soothing agent, and 0.5 parts of composite plant anti-allergic agent were added, and the inorganic nanoparticles were homogenized using a planetary vacuum mixer.

[0080] The filling degree in the autoclave used for the preparation of this embodiment is 70%, the prepared ZnO is wurtzite type, refractive index 1.9-2.0, particle size 50-60nm, the prepared SiO2 is α-quartz, refractive index 1.54-1.55, thickness 20-40nm, and the prepared TiO2 layer is anatase type, refractive index 2.50-2.55, thickness 10-30nm. The thickness distribution range of SiO2 and TiO2 is large because the surface of the angular nano zinc oxide column and the surface of the polyhedral nano zinc oxide microsphere have different crystal orientation preference levels, and the surface of the polyhedral nano zinc oxide microsphere is more suitable for planar growth, so it is thicker and suitable for UVA reflection. The shell layer of the surface of the angular nano zinc oxide column is thinner, so it is more suitable for UVB reflection.

[0081] Step S1-1: The nano silver quantum dots are attached to the surface of the polyhedral nano zinc oxide microspheres in a discrete manner to form seed crystal planes and epitaxial growth sites for lattice mismatch, providing a basis for the (0001) plane preferential orientation growth of angular nano zinc oxide. Hexadecyl trimethyl ammonium bromide provides the surface attachment ability of the nano silver quantum dots at low concentrations.

[0082] The increase in the concentration of zinc nitrate in step S1-2 will affect whether the corners of the angular nano zinc oxide are sharp or flat. The corner length is 150-180nm and the root width is 20-30nm. The crystal growth orientation is the (0001) plane. Since the hexagonal wurtzite structure zinc oxide crystals are generally composed of two crystal planes of different properties: two chemically active polar planes (0001) and (0001̅), and six chemically stable non-polar planes. Due to the presence of the polar axis, zinc oxide crystals are usually mainly columnar or conical crystals growing along the c-axis. The hydrothermal solvothermal method is a simple and effective method for controlling the microscopic morphology of zinc oxide crystals.

[0083] Figure 4 This is the SEM image of the composite nanoparticles of this embodiment. It can be seen that the angular nano zinc oxide columns significantly exceed the shell layer of the polyhedral nano zinc oxide microspheres. The angular protrusion structure, as an optical structure, increases the incident surface, which is equivalent to increasing the incident angle of small-angle incident light, thereby improving the reflection efficiency. At the same time, it is equivalent to reducing the exit angle of the total emitted light from the microsphere after the incident.

[0084] Figure 5 The schematic diagram of the structure theory of this embodiment. Finally, 1 is a polyhedral nano zinc oxide microsphere, 2 is the first layer of SiO2 shell, 3 is the second layer of TiO2 shell, 4 is the second layer of SiO2 shell, 5 is the second layer of TiO2 shell, and 6 is a mixed layer of other cosmetic components. The equivalent DBR structure of the ultraviolet path is a three-fold structure, part of which is reflected by the DBR structure and part enters the ZnO core and is absorbed. This structure filters ultraviolet rays of 280 to 370 nm (see Figure 6 (the spherical line).

[0085] Example 3 was prepared according to the method of Example 1, with the variable changed to 4 groups of SiO2 / TiO2 composite layers.

[0086] Comparative Example 1, preparing cosmetics containing ordinary nano zinc oxide sunscreen, the specific steps are as follows: First, 5 parts of glyceryl stearate, 10 parts of glycerol, and 20 parts of anhydrous ethanol are mixed by mechanical stirring, and then 15 parts of dicaprylyl carbonate, 8 parts of bis-ethylhexyloxyphenol methoxyphenyl triazine, and 8 parts of ethylhexyl methoxycinnamate are added. Finally, 40 parts of nano zinc oxide particles with a particle size of 50-70 nm, 1 part of aloe soothing agent, and 0.5 parts of composite plant antiallergic agent are added, and a planetary vacuum mixer is used to complete the homogenization of the inorganic nanoparticles.

[0087] Comparative Example 2, preparing cosmetics containing ordinary nano zinc oxide sunscreen, the specific steps are as follows: First, 5 parts of glyceryl stearate, 10 parts of glycerol, and 20 parts of anhydrous ethanol were mixed by mechanical stirring, and then 15 parts of dicaprylyl carbonate, 8 parts of bis-ethylhexyloxyphenol methoxyphenyl triazine, and 8 parts of ethylhexyl methoxycinnamate were added. Finally, 40 parts of nano zinc oxide particles with a particle size of 300-350 nm, 1 part of aloe soothing agent, and 0.5 parts of composite plant antiallergic agent were added, and a planetary vacuum mixer was used to complete the homogenization of the inorganic nanoparticles.

[0088] Comparative Example 3, preparing cosmetics containing ordinary nano zinc oxide sunscreen, the specific steps are as follows: First, 5 parts of glyceryl stearate, 10 parts of glycerol, and 20 parts of anhydrous ethanol were mixed by mechanical stirring, and then 15 parts of dicaprylyl carbonate, 8 parts of bis-ethylhexyloxyphenol methoxyphenyl triazine, 8 parts of ethylhexyl methoxycinnamate, 1 part of aloe soothing agent, and 0.5 parts of composite plant antiallergic agent were added, and a planetary vacuum mixer was used to complete the homogenization of the inorganic nanoparticles.

[0089] The sunscreen cosmetics prepared in the above-mentioned Experimental Examples 1 to 3 and Comparative Example 1 were subjected to sample preparation and testing. The test standard is as follows: The sun protection factor SPF of the prepared emulsion is obtained according to ISO24443:2021. 30 mg of the prepared sunscreen emulsion was evenly applied on a PMMA plate, and after drying for 15 minutes in a lightless environment, the SPF value between 290 and 400 nm was measured at 5 different positions on the PMMA plate. Three plates were coated with each sample, and the test results are shown in Table 1.

[0090] As can be seen from Table 1, when no physical sunscreen is added to Comparative Example 3, its SPF value is the lowest. Since Example 2 has obvious ultraviolet reflection effect in the range of 280-370nm, it can achieve SPF50 effect when the usage is relatively low. Since Example 3 increases the number of DBR reflection layers, it also brings a certain increase in ultraviolet reflectivity, so the sun protection level is increased. The minimum lengths of Examples 1-3 are all over 200nm, and theoretical calculations show that it is less than 200nm when there are only two groups of DBR reflection layers in Example 1. Therefore, the core-shell structure material of the present invention can largely avoid the biological toxicity problem caused by the penetration of nanopowder into the skin.

[0091] Table 1 Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A sunscreen cosmetic composition, characterized in that: The sunscreen cosmetics include the following components: 20-60 parts of physical sunscreen, 0-30 parts of chemical sunscreen, 0.01-1 parts of antioxidant, 5-20 parts of oil, 5-15 parts of moisturizer, 1-5 parts of emulsifier, 10-30 parts of anhydrous ethanol and 0.1-3 parts of other additives. The physical sunscreen is ZnO@DBR composite nanoparticles formed by polyhedral nano zinc oxide microspheres as cores and multilayer SiO2 / TiO2 periodic structures as shells.

2. A sunscreen cosmetic composition according to claim 1, characterized in that: The surface of the polyhedral nano zinc oxide microspheres is epitaxially provided with angular nano zinc oxide columns, which are then coated with multi-layer SiO2 / TiO2 periodic structures to form spherical ZnO@DBR composite nanoparticles.

3. A method for preparing the sunscreen cosmetic composition according to claim 1, characterized in that: The following steps are involved: S1: Synthesize nano zinc oxide microspheres by hydrothermal method, and form polyhedral nano zinc oxide microspheres by high temperature annealing in an inert atmosphere; S2: hydrothermal coating of SiO2 to form ZnO@SiO2 composite nanoparticles; S3: hydrothermal coating of TiO2 to form ZnO@SiO2@TiO2 composite nanoparticles; S4: Repeat steps S2 and S3 to form ZnO@DBR composite nanoparticles with a SiO2 / TiO2 composite layer having a stacking period greater than 2; S5: 20-60 parts of ZnO@DBR composite nanoparticles as physical sunscreen are mixed with 0-30 parts of chemical sunscreen, 0.01-1 parts of antioxidant, 5-20 parts of oil, 5-15 parts of moisturizer, 1-5 parts of emulsifier, 10-30 parts of anhydrous ethanol and 0.1-3 parts of other additives to prepare a sunscreen cosmetic composition.

4. The method for preparing the sunscreen cosmetic composition according to claim 3, characterized in that: Between step S1 and step S2, the following steps are also included: S1-1: Preparation of silver nanoparticles by hydrothermal method on the surface of polyhedral nano-zinc oxide microspheres to prepare lattice-mismatched growth surfaces; S1-2: hydrothermally epitaxially grow angular nano-zinc oxide on the growth surface.

5. The method for preparing the sunscreen cosmetic composition according to claim 3 or 4, characterized in that: The particle size of the nano zinc oxide microspheres prepared in step S1 is 50-70nm, the thickness of the SiO2 shell layer prepared in step S2 is 20-40nm, the thickness of the TiO2 shell layer prepared in step S3 is 10-30nm, and the SiO2 / TiO2 composite layer in step S4 is 2-4 groups.

6. The method for preparing the sunscreen cosmetic composition according to claim 3 or 4, characterized in that: The optical refractive index of the SiO2, chemical sunscreen, antioxidant, oil, moisturizer, emulsifier and other additives is less than 1.55, the optical refractive index of the TiO2 is greater than or equal to 2.50, and the optical refractive index of the zinc oxide is 1.9-2.

1.

7. The method for preparing the sunscreen cosmetic composition according to claim 4, characterized in that: The particle size of the nano silver quantum dots is 5 to 10 nm, the length of the angular nano zinc oxide is 150 to 180 nm, and the root width is smaller than the polyhedron particle size.

8. The method for preparing the sunscreen cosmetic composition according to claim 3 or 4, characterized in that: The zinc source used in step S1 is one or more of zinc nitrate, zinc acetate and zinc chloride, the silicon source used in step S2 is one or more of tetraethyl orthosilicate, rice husk ash and water glass, and the titanium source used in step S3 is one or more of tetrabutyl titanate, titanium tetrachloride and titanium sulfate.

9. The method for preparing the sunscreen cosmetic composition according to claim 3 or 4, characterized in that: The chemical sunscreen in step S5 includes UVA and UVB sunscreens, wherein the UVA sunscreen is composed of one or more of bis-ethylhexyloxyphenol methoxyphenyl triazine, butyl methoxydibenzoylmethane, diethylaminohydroxybenzoyl hexyl benzoate, and butyl methoxybenzophenone, and the UVB sunscreen is composed of one or more of phenylbenzimidazole sulfonic acid, ethylhexyl salicylate, octyl salicylate, ethylhexyl methoxycinnamate, octyl dimethyl para-aminobenzoate, homosalate, polysiloxane, and octyl triazone.

10. The method for preparing the sunscreen cosmetic composition according to claim 3 or 4, characterized in that: The antioxidant in step S5 is composed of one or more of propylparaben, methylparaben, phenoxyethanol, benzyl alcohol, bis(hydroxymethyl)imidazolidinyl urea, and iodopropynyl butylcarbamate, the oil is composed of one or more of dicaprylyl carbonate, dipropylene glycol dibenzoate, octyl polymethylsiloxane, cyclopentasiloxane, and tridecyl stearate, the moisturizer is composed of one or more of glycerol, propylene glycol, butylene glycol, betaine, panthenol, and sodium hyaluronate, the emulsifier is composed of one or more of glyceryl stearate, polyglyceryl-3 diisostearate, cetearyl glucoside, and sorbitan olivate, and the other additives are composed of one or more of soothing agents, anti-allergic agents, chelating agents, cross-linking agents, and flavors.

Citation Information

Patent Citations

  • A nano-core-shell structured composite material for cosmetics and its preparation method

    CN102274129A

  • Sunscreening granule with TiO2-HA core-shell structure as well as preparation method and application thereof

    CN103110535A

  • Hybrid microsphere with functions of reflecting, scattering and absorbing ultraviolet rays and applications of hybrid microsphere

    CN107374987A

  • Sunscreen skin care product and preparation method thereof

    CN112353699A

  • Natural polyphenol functionalized antioxidant composite sun-screening agent and preparation method thereof

    CN113143785A